I spy fantasy : a book of picture riddles - Wick, Walter; Marzollo, Jean. (New York : Scholastic, 1994)
Rhyming verses invite readers to "spy" particular items in photographs containing dozens of toys and objects.
"Cartwheel Books."
Wilson's Children
Elem. School Library Collection
School Library Journal
2.5
3-6
Keywords: Picture puzzles -- Juvenile literature; Picture puzzles; Picture puzzles